Comparison of Luxury Perception in the Czech and Russian markets - Bashirova, Anastasiia; Escobar Rios, Andrea; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how luxury value perception varies between Czech and Russian consumers, with the aim of identifying market-specific priorities and providing practical guidance for brand positioning. Drawing on Wiedmann et al.’s (2013) four-dimensional model—comprising financial, functional, individual, and social value—and Keller’s (2001) brand resonance framework, the study explores how these dimensions influence the development of strong consumer-brand relationships. Primary data were collected through a quantitative survey targeting young potential consumers in both countries. The findings reveal a shared emphasis on functional value, but diverging secondary priorities: Czech respondents lean toward pragmatic and investment-driven views of luxury, while Russian respondents express stronger emotional and self-expressive motivations. These insights are used to outline strategic implications for luxury brands planning to operate in these two markets.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses